Pelatihan Pembuatan Proses Bisnis Aplikasi Rencana, Pengendalian, Dan Evaluasi Pembangunan Daerah Pada Bapperida Provinsi Sumatera Utara - Edrian Hadinata; Dedy Irwan; Andi Marwan Elhanafi; Ahmad Zakir (JUBDIMAS ( Jurnal Pengabdian Masyarakat), 2026)
The development of the Regional Development Planning, Control, and Evaluation Application requires a clear business-process design before the system is translated into software modules, databases, access rights, and monitoring dashboards. This community service activity aimed to strengthen the capacity of civil servants and government employees with work agreements at the Regional Development Planning, Research and Innovation Agency (BAPPERIDA) of North Sumatra Province in identifying, documenting, and validating the business processes required for application. The activity was implemented through needs identification, interactive lectures, case-based workshops, cross-functional process mapping, group mentoring, presentations, and reflective evaluation. The training materials covered the legal and conceptual basis of regional development control and evaluation, linkages among RPJMD, RKPD, Renstra, Renja, and DPA/APBD, system architecture, user roles, quarterly reporting, verification, performance and deviation analysis, evaluation, recommendations, executive reporting, follow-up monitoring, and data governance. The qualitative results indicate that participants were able to formulate a shared understanding of the end-to-end process, identify actors and decision points, map inputs and outputs, and prepare an initial cross-functional process design for application development. Based on the Paired Samples t-test results, there was a significant difference in participants’ competencies before and after attending the training on developing the business process for the Regional Planning, Control, and Evaluation Application. The participants’ mean score increased from 62.18 on the pretest to 66.95 on the posttest. The training contributes to strengthening process-oriented governance and provides an initial foundation for developing an integrated, accountable, and data-driven application.